Tenofovir Versus Placebo to Prevent Perinatal Transmission of Hepatitis B. Issue 3 (September 2018) - Jourdain, G.; Ngo-Giang-Huong, N.; Harrison, L.; Decker, L.; Khamduang, W.; Tierney, C.; Salvadori, N.; Cressey, T.R.; Sirirungsi, W.; Achalapong, J.; Yuthavisuthi, P.; Kanjanavikai, P.; et al.
Abstract : ( N Engl J Med 2018;378:911–923) Despite vaccination and administration of hepatitis B immune globulin at birth, mother-to-child transmission of hepatitis B virus (HBV) can still occur, specifically in infants born to women who test positive of hepatitis B e antigen (HBeAg), have a high HBV viral load (>200, 000 IU/mL), or have a mutant HBV strain that escapes the vaccine or immune globulin. Antiviral agents like lamivudine, tenofovir disoproxil fumarate (TDF), and telbivudine have been used prophylactically in pregnant women with high HBV viral loads. However, the evidence on the relative benefits or harm of this intervention are limited or of low quality. Therefore, these authors present the results of a clinical trial, in which they assessed the efficacy and safety of TDF in the prevention of mother-to-child HBV transmission in pregnant women positive for HBeAg.